2013
DOI: 10.1080/19424280.2013.766649
|View full text |Cite
|
Sign up to set email alerts
|

Barefoot running – some critical considerations

Abstract: The purpose of this paper is to discuss critically selected aspects of the current discussion on barefoot running, specifically differences between barefoot and shod running in kinematics and kinetics, training effects, performance and economy and injury frequency.The kinematics and kinetics depend on many different factors, including surface, shoe, running speed and subject. In general, hard surfaces are associated with a flatter foot landing. However, the inter-individual differences are substantial and it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 28 publications
(43 reference statements)
0
27
0
Order By: Relevance
“…gait retraining had no effect on RE (Ardigo et al, 1995;Fletcher et al, 2008;Gruber et al, 2013;Messier & Cirillo, 1989), or may even make RE worse (Cavanagh & Williams, 1982;Dallam et al, 2005;Tseh, Caputo, & Morgan, 2008). To support these studies, Nigg and Enders (2013) and Saunders et al (2004) have suggested that self-selected running kinematics rather than deliberate changes are more appropriate for optimizing RE. This may be because deliberate changes result in deviations from the preferred movement pathway that has been dictated by physiological and neuromuscular adaptations to repeated training (Saunders et al, 2004) that will not be optimized immediately (Bonacci, Chapman, Blanch, & Vicenzino, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…gait retraining had no effect on RE (Ardigo et al, 1995;Fletcher et al, 2008;Gruber et al, 2013;Messier & Cirillo, 1989), or may even make RE worse (Cavanagh & Williams, 1982;Dallam et al, 2005;Tseh, Caputo, & Morgan, 2008). To support these studies, Nigg and Enders (2013) and Saunders et al (2004) have suggested that self-selected running kinematics rather than deliberate changes are more appropriate for optimizing RE. This may be because deliberate changes result in deviations from the preferred movement pathway that has been dictated by physiological and neuromuscular adaptations to repeated training (Saunders et al, 2004) that will not be optimized immediately (Bonacci, Chapman, Blanch, & Vicenzino, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…Unfortunately, the etiology of running-related injuries is not well understood. Previous research has reported that increasing age, female gender, previous injury, high BMI, low fitness level, foot posture, and excessive training distance are associated with injury [1][2][3]. Previous research has also suggested that pronation or pronation rate may be associated with injury [4,5], and this belief has led to the development of running shoes aimed at reducing pronation (e.g., motion control shoes).…”
Section: Introductionmentioning
confidence: 95%
“…Running-related injuries such as medial tibial stress syndrome (''shin splints''), patellofemoral pain syndrome (''runner's knee''), Achilles tendonitis, plantar fasciitis, and iliotibial band syndrome have been reported to affect approximately 20-79% of runners on an annual basis [1,2]. Unfortunately, the etiology of running-related injuries is not well understood.…”
Section: Introductionmentioning
confidence: 97%
“…Whilst BFT gait adjustments have been reported to reduce injury likelihood (Lieberman et al 2010, Robbins & Hanna 1987, there is no conclusive evidence to support this notion (Nigg & Enders 2013). In fact, there is some evidence of an increase in peak tibial acceleration when running BFT compared with SH (McNair & Marshall 1994, Sinclair et al 2013a.…”
Section: Introductionmentioning
confidence: 65%
“…A recent review concluded that currently there is no consensus in the literature regarding the affect that BFT and/or MS running has on running economy (RE) (Nigg & Enders 2013), a crucial factor in determining performance in long distance running events (Conley & Krahenbuhl 1980). The differing methodologies are perhaps, in part, the reason for contrasting evidence.…”
Section: Introductionmentioning
confidence: 99%